If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + 7 = -6 + -56 Reorder the terms: 7 + 3g = -6 + -56 Combine like terms: -6 + -56 = -62 7 + 3g = -62 Solving 7 + 3g = -62 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3g = -62 + -7 Combine like terms: 7 + -7 = 0 0 + 3g = -62 + -7 3g = -62 + -7 Combine like terms: -62 + -7 = -69 3g = -69 Divide each side by '3'. g = -23 Simplifying g = -23
| 30+1.95x=7.95x | | ln(-2x)=7 | | -5+32x^2-24x^2+44=6x | | x*9+12=x*4+162 | | 25-x-19=26-5x-6x | | 7x^7-56x^6+42x^5= | | 165-7x=20x+15 | | 10-10x=118-38x | | 2x-x+8x= | | 179-5x=6x+14 | | 9(x-3)+8(x+6)=4(8-7x) | | 0.1(x+100)+0.1x=1 | | -1*[-2]=x | | -36-2x+9x=3x+12 | | 5(t-2)-3t=4(2+4)-9 | | 4(2x+9)=20 | | 8a^2+4a= | | 9+n=2n-4 | | 9-10x=94-45x | | (x+2)(2x-3)=0 | | 4x-11x+7=4 | | 5(x+2)+x=3(x-1)+1 | | 24+0.99x=1.49x | | 4(v-3)-6v=-2(v+6) | | 15=-8(c-1)+9 | | x^6-9x^3+20=0 | | 4(v-3)-6v=2(v+6) | | 5(2+y)-y=10+4(y+1) | | 8(2x+3)=56 | | 4x^3+22x^2+52x=0 | | 7(2k-1)+4=7 | | -2(w+4)+6w=4(w-3) |